2021
DOI: 10.1038/s41525-021-00249-x
|View full text |Cite
|
Sign up to set email alerts
|

Immune cell infiltration signatures identified molecular subtypes and underlying mechanisms in gastric cancer

Abstract: Increasing evidence has clarified that the tumor microenvironment (TME) is closely related to the prognosis and therapeutic efficacy of cancer. However, there is no reliable TME evaluation system used to accurately predict the prognosis of and therapeutic efficacy in gastric cancer. We evaluated the immune microenvironment score (IMS) of 1422 gastric cancer samples based on 51 immune cell signatures. We explored the relationship between the IMS and prognosis, immune cell infiltration, cancer subtype, and poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…A better understanding of antitumor immunity will help predict the prognosis of gastric cancer patients and customize the appropriate therapies in each patient. Therefore, immune profiling of gastric cancer and immunological classification were extensively studied [ [6] , [7] , [8] , [9] ]. Previously, we also proposed a novel immunological classification of gastric cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…A better understanding of antitumor immunity will help predict the prognosis of gastric cancer patients and customize the appropriate therapies in each patient. Therefore, immune profiling of gastric cancer and immunological classification were extensively studied [ [6] , [7] , [8] , [9] ]. Previously, we also proposed a novel immunological classification of gastric cancer [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular subtyping systems focusing on immune infiltrating signatures have emerged to stratify patients and predict prognosis and immunotherapeutic outcomes in various tumors ( 55 57 ). However, these subtyping systems failed to depict detailed immune profiles in TME, which are important for understanding the mechanisms by which immune cells modulate tumor progression and response to ICB therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with other subgroups, patients with high TMB/high m6Ascore have the worst prognosis, which also shows that the TMB status does not affect the prognostic value of m6Ascore. m6Ascore has the potential to predict immunotherapy responsiveness, which may be independent of TMB ( Zhang et al, 2020 ; Guan et al, 2021 ; Lin et al, 2021 ; Sun et al, 2021 ; Wu et al, 2021 ). In addition, the TIDE results suggested that the patients in the low-risk group may respond better to immunotherapy.…”
Section: Discussionmentioning
confidence: 99%